Recent advances in Raman and surface enhanced Raman spectroelectrochemistry - Yue, Kang; Weipeng, Wang; Tian, Ma; Ting, Zou; Junxian, Chen; Zhengjun, Zhang (Frontiers in Nanotechnology, 2023)
Raman spectroscopy could supply the molecular vibrational process giving the detailed information of molecular structure. At the same time, electrochemistry could provide kinetic and thermodynamic processes. Integration of both technology with the general definition of using spectroscopic approaches for assaying the variations triggered through an electrochemistry-based system within an electrochemical cell induces a novel technique, spectroelectrochemistry (SEC). Raman-SEC possesses interdisciplinary advantages and can further expand the scopes in the fields of analysis and other applications, emphasizing the cutting-edge issues of analytical chemistry, materials science, biophysics, chemical biology, and so on. This review emphasizes on the recent progress of integrated Raman/SERS-SEC and aimed to summarize the SEC device, electrode materials and applications of Raman/SERS-SEC over the past several decades. Finally, the key issues, future perspectives and trends in the development of Raman/SERS-SEC are discussed.